A Comparison of Walking Rates Between Wild and Zoo African Elephants. Issue 3 (2nd July 2016) - Miller, Lance J.; Chase, Michael J.; Hacker, Charlotte E.
Abstract : With increased scrutiny surrounding the welfare of elephants in zoological institutions, it is important to have empirical evidence on their current welfare status. If elephants are not receiving adequate exercise, it could lead to obesity, which can lead to many issues including acyclicity and potentially heart disease. The goal of the current study was to compare the walking rates of elephants in the wild versus elephants in zoos to determine if elephants are walking similar distances relative to their wild counterparts. Eleven wild elephants throughout different habitats and locations in Botswana were compared to 8 elephants at the San Diego Zoo Safari Park. Direct comparisons revealed no significant difference in average walking rates of zoo elephants when compared with wild elephants. These results suggest that elephants at the San Diego Zoo Safari Park walk similar rates to those of wild elephants and may be meeting their exercise needs.